Deterministic processes dominate archaeal community assembly from the Pearl River to the northern South China Sea - Lin, Xizheng; Zhang, Chuanlun; Xie, Wei (Frontiers in Microbiology, 2023)
Archaea play a significant role in the biogeochemical cycling of nutrients in estuaries. However, comprehensive researches about their assembly processes remain notably insufficient. In this study, we systematically examined archaeal community dynamics distinguished between low-salinity and high-salinity groups in water and surface sediments over a 600-kilometer range from the upper Pearl River (PR) to the northern South China Sea (NSCS). Neutral community model analysis together with null model analysis showed that their C-score values were greater than 2, suggesting that deterministic processes could dominate the assembly of those planktonic or benthic archaeal communities at both the low-salinity and high-salinity sites. And deterministic processes contributed more in the low-salinity than high-salinity environments from the PR to the NSCS. Furthermore, through the co-occurrence network analysis, we found that the archaeal communities in the low-salinity groups possessed closer interactions and higher proportions of negative interactions than those in the high-salinity groups, which might be due to the larger environmental heterogeneities reflected by the nutrient concentrations of those low-salinity samples. Collectively, our work systematically investigated the composition and co-occurrence networks of archaeal communities in water as well as sediments from the PR to the NSCS, yielding new insights into the estuary's archaeal community assembly mechanisms.